How to make money from your stock investment even in the falling market - Ho, Kok Mun (Kanyin Publications, 2004)
Whether you are fresh graduate, working professional, middle aged or folks, everyone wants better investment methods which are able to bring you the maximum return within shortest period possible. With so many investment options you can choose in the market, you want to make sure your money is working hard and give you the return you are meaning for. But yet stock investment is a great sources of confusion for many. Many equate investing in stock to gambling, therefore is extremely risky. The fact is, investing is not risky at all, and it's only so if it's done without proper knowledge and understanding Ho Kok Mun is going to show how you can even make money in the bear market, with return up to 30% He'll reveal the strategies behind his selection of his stocks, how you can maximise your return in the stock market. even when the market is falling Find out the techniques of buying undervalued quality stocks, how to determine when is the right price to buy, sell or to hold the stocks. You'll learn how to achieve all that without leaving your current job and still be able to enjoy comfortable continuous passive income.